Ukraine as object and subject of geopolitics: the problem of choice - Власенко, Т. Т. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
We consider both internal and external causes of the crisis in Ukraine. The author analyzes geopolitical situation in the world, trends and forecasts for the world system and its impact on the solution to the crisis in the Ukrainian society. Considers possible models of development of Ukraine. Among the internal causes focuses on the language and cultural factors forming the universal conceptual oppositions political discourse in Ukraine.